Analysis of Health Risk Factors among Intercity Bus Drivers During the 2024 Eid al-Fitr Holiday Season in East Jakarta - Rani Sulastri; Dadan Erwandi; Doni Lasut (Eduvest - Journal of Universal Studies, 2025)
Driver health checks are crucial to ensure the safety and well-being of individuals operating vehicles, especially those in public transportation professions, such as intercity and interprovincial buses (AKAP) and similar modes of transportation, to prevent the risk of road accidents. This study aims to analyze the relationship between driver health risk factors—namely age, blood sugar levels, and amphetamine in urine—and driving fitness during the Eid al-Fitr season at two intercity bus terminals in East Jakarta Administrative City during the 2024 Eid al-Fitr season. Data collection was conducted through surveillance from April 3, 2024, to April 17, 2024, involving 667 drivers, and analyzed using univariate and bivariate methods with JASP software. The results showed that 76.6% of drivers had mild to severe hypertension, 7.8% had blood sugar levels >200 mg/L, 0.4% tested positive for respiratory alcohol, and 0.3% tested positive for amphetamine. As a recommendation, 11.1% of drivers were deemed unfit to drive. Hypertension, blood glucose levels, and driving fitness were statistically associated with driver age (p < 0.001). Age, as a confounding factor, is closely related to the measured parameters and driving fitness, necessitating attention to reduce the risk of road accidents, particularly during the Eid al-Fitr holiday period. These findings highlight the critical need for regular health monitoring of aging commercial drivers and the implementation of age-specific fitness assessment protocols to enhance road safety during high-traffic holiday periods.